Genetic analysis of the atrial natriuretic peptide gene polymorphisms among essential hypertensive patients in Malaysia - Ghodsian, Nooshin; Ismail, Patimah; Ahmadloo, Salma; Eskandarian, Narges; Etemad, Ali (Hindawi Publishing Corporation, 2016)
Background. Atrial natriuretic peptide (ANP) considerably influences blood pressure regulation through water and sodium homoeostasis. Several of the studies have utilized anonymous genetic polymorphic markers and made inconsequent claims about the ANP relevant disorders. Thus, we screened Insertion/Deletion (ID) and G191A polymorphisms of ANP to discover sequence variations with potential functional significance and to specify the linkage disequilibrium pattern between polymorphisms. The relationships of detected polymorphisms with EH with or without Type 2 Diabetes Mellitus (T2DM) status were tested subsequently. Method. ANP gene polymorphisms (I/D and A191G) were specified utilizing mutagenically separated Polymerase Chain Reaction (PCR) in 320 subjects including 163 EH case subjects and 157 controls. Result. This case-control study discovered a significant association between I/D polymorphisms of ANP gene in EH patient without T2DM. However, the study determined no association between G191A polymorphisms of ANP in EH with or without T2DM. In addition, sociodemographic factors in the case and healthy subjects exhibited strong differences (). Conclusion. As a risk factor, ANP gene polymorphisms may affect hypertension. Despite the small sample size in this study, it is the first research assessing the ANP gene polymorphisms in both EH and T2DM patients among Malaysian population.